Respon Pertumbuhan Spesies C3 dan C4 terhadap Cekaman Kekeringan dan Konsentrasi CO2 tinggi - Hamim Hamim (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2005)
Growth response of two C3 (wheat and kale) and two C4 species (Echinochloa crusgallii and Amaranthus caudatus) were analyzed in response to drought stress under different CO2 concentrations, i.e. ambient (350 ppm) and double ambient (700 ppm).  Drought was given by withholding water for several days until the plants were wilted.  Drought stress reduced relative water content (RWC), water potential (Yw), osmotic potential (Ys), net photosynthesis (Pn) and plant growth of all species.  During moderate drought Pn of C3 species decreased considerably, while that of C4 species was still sustained, suggesting that C4 cycle is important to sustain Pn during the beginning of the drought.  Doubled [CO2] enhanced growth of all species indicated by increase of plant height and leaf area, but the growth of C3 species was higher than that of C4 one.  Increase of growth due to high [CO2] was associated with an increase of Pn in C3 species but not in C4 species.  High [CO2] caused C4 species had RWC, Yw and Ys higher than C3 species during drought stress.  Increase of growth in C4 species may be associated by an increase of plant water status due to high [CO2].